2022
DOI: 10.1111/cjag.12314
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of production efficiency: Evidence from Irish farms

Abstract: The objective of this paper is to investigate the economics of production efficiency of dairy farms, with a specific focus on the role of agricultural policy. Our analysis is based on a representative sample of Irish dairy farms, ranging from 2000 to 2018, which includes a period of major change in EU dairy policy. Based on a multi-input multi-output production system, we first estimate technical, allocative, scale and scope efficiencies. We find significant heterogeneity in technical and allocative efficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…In addition to management, AFC is low to moderate heritability in beef cows ranging from 10% to 27% ( Heise et al, 2018 ; Brzáková et al, 2020 ; Shin et al, 2021 ). Although improvements in management on beef herds ( Martinez Cillero et al, 2018 ; Chavas et al, 2022 ) and genetic merit of AFC in beef heifers ( de Rezende et al, 2020 ; Twomey et al, 2020 ) have been observed, the AFC of beef cows is still higher than 24 mo in some beef herds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to management, AFC is low to moderate heritability in beef cows ranging from 10% to 27% ( Heise et al, 2018 ; Brzáková et al, 2020 ; Shin et al, 2021 ). Although improvements in management on beef herds ( Martinez Cillero et al, 2018 ; Chavas et al, 2022 ) and genetic merit of AFC in beef heifers ( de Rezende et al, 2020 ; Twomey et al, 2020 ) have been observed, the AFC of beef cows is still higher than 24 mo in some beef herds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the design of environmental aid is at the Member State's discretion, research is needed to further investigate whether and to what extent the ambiguous empirical evidence concerning this category of payments (with positive, negative, or nonsignificant effects, e.g., Chavas et al, 2022; Latruffe & Desjeux, 2016; Martinez Cillero et al, 2021) could be determined by national policy design, affecting the inherent tensions of these subsidies, between the drive toward efficiency and that toward sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Chavas et al (2022) carry out a multioutput (milk, calves, cattle, sheep, and crops) analysis of Irish dairy farms, over the period 2000-2018, adopting a two-step procedure. First, they estimate certain efficiency measures using a nonparametric approach, then they assess the relevance of certain determinants adopting a censored regression with random effects.…”
mentioning
confidence: 99%
“…La identificación de factores que optimizan la eficiencia productiva de las granjas lecheras es de gran importancia para aumentar la productividad y la rentabilidad y proteger el bienestar animal y el medio ambiente [1]. La eficiencia productiva se puede definir como una parte integral del uso de recursos escasos y de tecnología avanzada para mejorar la producción de alimentos para sustentar a una población mundial en crecimiento [2].…”
Section: Introductionunclassified